2005
DOI: 10.1111/j.1365-3156.2005.01500.x
|View full text |Cite
|
Sign up to set email alerts
|

Repellent properties of celery, Apium graveolens L., compared with commercial repellents, against mosquitoes under laboratory and field conditions

Abstract: SummaryIn our search for new bioactive products against mosquito vectors, we reported the slightly larvicidal and adulticidal potency, but remarkable repellency of Apium graveolens both in laboratory and field conditions. Repellency of the ethanolic preparation of hexane-extracted A. graveolens was, therefore, investigated and compared with those of 15 commercial mosquito repellents including the most widely used, DEET. Hexane-extracted A. graveolens showed a significant degree of repellency in a dosedependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 19 publications
0
46
0
Order By: Relevance
“…The complete protection of ZPOv against the predominant A. subalbatus and other mosquito vectors, A. gardnerii, C. gelidus, C. tritaeniorhynchus, C. vishnui group, and M. uniformis, was also promising. When compared with other field studies, the complete protective effect of ZPOv against A. subalbatus seems to be comparable to results of hexane-extracted Apium graveolens (Tuetun et al 2005) and exceeds those of the neem oil (37.5%) and ethanol-extracted Curcuma aromatica (89.69%) tested in the studies of Sharma et al (1995) and Pitasawat et al (2003), respectively. In this study, ZPOv and 25% DEETv probably protected against other mosquito species comprising Aedes albopictus, Aedes lineatopennis, Anopheles peditaeniatus, Anopheles tesellatus, C. quinquefasciatus, and Mansonia annulifera, which were only collected from the controls.…”
Section: Discussionmentioning
confidence: 77%
“…The complete protection of ZPOv against the predominant A. subalbatus and other mosquito vectors, A. gardnerii, C. gelidus, C. tritaeniorhynchus, C. vishnui group, and M. uniformis, was also promising. When compared with other field studies, the complete protective effect of ZPOv against A. subalbatus seems to be comparable to results of hexane-extracted Apium graveolens (Tuetun et al 2005) and exceeds those of the neem oil (37.5%) and ethanol-extracted Curcuma aromatica (89.69%) tested in the studies of Sharma et al (1995) and Pitasawat et al (2003), respectively. In this study, ZPOv and 25% DEETv probably protected against other mosquito species comprising Aedes albopictus, Aedes lineatopennis, Anopheles peditaeniatus, Anopheles tesellatus, C. quinquefasciatus, and Mansonia annulifera, which were only collected from the controls.…”
Section: Discussionmentioning
confidence: 77%
“…It appeared not to cause dermal irritation or any other adverse effect, either during 6 months of use or in the following 3 months of follow-up. Further studies demonstrated that the ethanolic preparation of hexane-extracted A. graveolens displayed a significant degree of repellency in a dose-dependent manner with vanillin added (Tuetun et al 2005). Ethanolic A. graveolens formulations (10-25 % with and without vanillin) provided 2-5 h protection against female Aedes aegypti.…”
Section: Insect Repellencymentioning
confidence: 98%
“…Unfortunately, there is currently no natural product that can give superior or comparable repellency to that of DEET (Novak and Gerberg 2005). When freshly applied to human skin, citronella or citronella-based repellents are about as effective as the synthetic chemicals in repelling some biting insects but for only approximately 1 h (Rozendaal 1997;Tuetun et al 2005). In addition to advantages such as being selective, easily biodegradable, and doing little or no harm to nontarget organisms, herbal-based products, with a potential source of bioactive chemicals and general use as fragrances and flavoring agents for food and beverages, have been recommended as an alternative source of materials for insect control (Isman 2000;.…”
Section: Introductionmentioning
confidence: 99%